Transformational Leadership of Kiai in Pesantren Management: A Qualitative Study of Islamic Educational Management - Agung Syarifudin; Anna Setiani; Siti Khoirotun Nafi’ah; Busthomi Ibrohim (al-Afkar, Journal For Islamic Studies, 2026)
In the era of educational disruption, pesantren are required to transform without losing their traditional (salaf) identity. The role of the Kiai as a central leader is a determinant factor in the success of such change management. Purpose: This study aims to analyze the implementation of the Kiai's transformational leadership in pesantren management, specifically in the aspects of institutional vision development and human resource empowerment. Methods: This research employs a qualitative approach with a descriptive case study design. Data were collected through in-depth interviews with the Kiai, foundation board members, and teachers, as well as through participatory observation and documentation. Data analysis used the Miles, Huberman, and Saldana model, including data condensation, data display, and drawing conclusions. Data validity was tested through source and technique triangulation. Findings: The research findings indicate that the Kiai's transformational leadership is operationalized through four main dimensions: (1) Idealized Influence through moral excellence and spiritual charisma; (2) Inspirational Motivation through the internalization of values of sincerity and independence; (3) Intellectual Stimulation by encouraging managerial ijtihad in the curriculum; and (4) Individualized Consideration through a humanistic paternalistic approach. The Kiai successfully integrates pesantren values with modern management principles (POAC) to enhance institutional competitiveness. Conclusion/Implications: This study concludes that the transformational leadership model in pesantren is unique, characterized by a blend of theological authority and managerial professionalism. The implications of this research strengthen transformational leadership theory within the context of non-formal Islamic educational organizations.